Modelling enterprise architectures - Holt, Jon; Perry, Simon (The Institution of Engineering and Technology, 2010)
The book reviews developments in the following fields: enterprise architecture (EA) modelling; introduction to the notation; UML diagrams; essential elements for an EA; requirements modelling for EAs; the Zachman framework; and defence-based architectural frameworks.